The heart in sporadic inclusion body myositis: a study in 51 patients - Cox, Fieke M. (Springer-Verlag, 2009)
The purpose of this study was to explore the prevalence and nature of cardiac abnormalities in sporadic inclusion body myositis (sIBM). Fifty-one sIBM patients were cross-sectionally studied using history-taking, physical examination, measurements of serum creatine kinase activity, the MB fraction (CK-MB), cardiac troponin T (cTnT) and I (cTnI), a 12-lead electrocardiogram (ECG) and 2-dimensional echocardiography. Present cardiac history was abnormal in 12 (24%) out of 51 patients, 12 (24%) patients had abnormalities on ECG, mostly aspecific, and in 12 (24%) patients the echocardiograph showed abnormalities. Elevated CK-MB was present in 42 (82%) patients and 40 (78%) had an elevated cTnT in the absence of acute cardiac pathology. In contrast, in one patient (2%) cTnI was elevated. There was no apparent association between elevated biomarkers, ECG or echocardiographic abnormalities. The prevalence of cardiac abnormalities in sIBM does not seem to be higher than would be expected in these elderly patients. Elevated CK-MB and cTnT levels are common, in contrast to cTnI, but do not reflect cardiac pathology.